Actualization of Environmental Education According to the Qur'an Through the SWALIBA Program at Madrasah Aliyah Darul Ilmi - Muhammad Efendi; Nasruddin Nasruddin; Muniratul Mukaramah; Asse Padly; Muhammad Sulaiman Jazuli (Abjadia, 2022)
Schools with Environmental Insight and Disaster Mitigation are schools that have a commitment and systematically internalize environmental values and disaster preparedness into all school activities. Madrasah Aliyah Darul Ilmi is in a transitional area of peat swamp with a plain area type that is very prone to disasters, the topography is very risky for floods, cyclones, and land fires. This study used a descriptive method with the approach of (1) counseling and discussion; (2) training; (3) simulation; (4) assistance; and (5) evaluation. Furthermore, the stages in this approach are tested through a questionnaire and visualized in the form of percentage data (%), The results obtained in the form of the level of understanding and attitudes of students towards the actualization of environmental education according to the Qur'an through the SWALIBA program. The results of this study are described as follows: (1) on the indicators of the importance of the environment for the life of students' ability to actualize themselves is Very Good with an accumulation percentage of 96.23%, this percentage has a correlation with very good knowledge and attitudes towards the environment and able to actualize it in life. (2) on indicators of sensitivity and understanding of disaster mitigation, students' actualization abilities are classified as Good with an accumulation percentage of 89.48%. This percentage correlates with the knowledge and attitudes shown by students during the school environment.